Student Performance Measure by Using Different Classification Methods of Data Mining - et. al., Ashutosh Mishra, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The assessment in outcome based learning is very vital and significant approach toward measuring the student’s performance. There are many traditional methods existing in this context. The data mining is one of the intelligent computing methods which are having widely accepted features that enable the idea of its usage in assessment. Much work has been done to measure the student performance by using different methodologies and modern technologies. In this work, we have gone through the current datasets of students of the university and different classification methods of data mining are used to measure the accuracy of student performance. Based on the analysis of the result, it has been concluded that accuracy and the other measures of SVM is more than the other classification methods.